(untitled) (International Journal of Engineering Materials and Manufacture, 2021)
By virtue of high-strength verses weight ratio aluminium alloys are achieving attentions in automobile, marine, and aircraft industries as it reduces the fuel consumption for running the vehicles. But their main drawback is the destruction of their carefully engineered microstructures by high heat generated in traditional welding processes. Friction Stir Welding (FSW) minimizes excessive heat in the welding zone and does notÂ Â influence the microstructural features.Â FSW is currently one of the recommended solutions for manufacturing aluminium alloy welded machine parts. In this study, AA6061 Al-alloy strips were lap joined using the improvised FSW setup tool clamping it on the spindle of a CNC milling machine with the speed rate varied from 1000 rpm to 3000 rpm, and three different feed rates 5, 15, and 25 mm/min. Shear strength experiments of these joints revealed that samples created with the speed rate of 1000 rpm and feed rate of 25 mm/min performed best showing the highest load carrying capacity of 8976 N with elongation of 1.04%. They also demonstrated highest Vickers hardness value of 31 at the centre of the weldment.